Opioid Utilization and Opioid-Related Adverse Events in Non-Surgical Patients in U.S. Hospitals - Herzig, Shoshana J. (2013)
BACKGROUND: Recent studies in the outpatient setting have demonstrated high rates of opioid prescribing and overdose-related deaths. Prescribing practices in hospitalized patients are unexamined. OBJECTIVE: To investigate patterns and predictors of opioid utilization in non-surgical admissions to U.S. hospitals, variation in use, and the association between hospital-level use and rates of severe opioid-related adverse events. DESIGN, SETTING, AND PATIENTS: Adult non-surgical admissions to 286 U.S. hospitals. MEASUREMENTS: Opioid exposure and severe opioid-related adverse events during hospitalization, defined using hospital charges and ICD-9-CM codes. RESULTS: Of 1.14 million admissions, opioids were used in 51%. The mean ± s.d. daily dose received in oral morphine equivalents (OME) was 68 ± 185 mg; 23% of exposed received a total daily dose of ≥ 100 mg OME. Opioid prescribing rates ranged from 5% in the lowest to 72% in the highest prescribing hospital (mean 51% ± 10%). After adjusting for patient characteristics, the adjusted opioid prescribing rates ranged from 33–64% (mean 50% ± s.d. 4%). Among exposed, 0.97% experienced severe opioid-related adverse events. Hospitals with higher opioid prescribing rates had higher adjusted relative risk of a severe opioid-related adverse event per patient exposed (RR 1.23 [1.14–1.33] for highest compared to lowest prescribing quartile). CONCLUSIONS: The majority of hospitalized non-surgical patients were exposed to opioids, often at high doses. Hospitals that used opioids most frequently had increased adjusted risk of a severe opioid-related adverse event per patient exposed. Interventions to standardize and enhance the safety of opioid prescribing in hospitalized patients should be investigated.